REFORM OF THE STUDY OF GEODESY AT THE DEPARTMENT OF GEODESY OF FACULTY OF CIVIL ENGINEERING, UNIVERSITY OF SARAJEVO - Džanina Omićević; Nedim Tuno (Geodetski Glasnik, 2011)
This paper presents activities and goals related with the implementation of the Bologna process at the Department of Geodesy of Civil Engineering, University of Sarajevo. For the first time, new curricula study of geodesy which are organized into three cycles: bachelor, master and postgraduete doctoral study are presented. The goal of this paper is to present basic informacion about ongoing reform proces, and that should change the long-term European university system.